2021
DOI: 10.1111/1756-185x.14081
|View full text |Cite
|
Sign up to set email alerts
|

Utility of magnetic resonance imaging in Crohn's associated sacroiliitis: A cross‐sectional study

Abstract: Objective Prevalence of sacroiliitis in Crohn's disease (CD) is variable depending on defining criteria. This study utilized standardized sacroiliac joint (SIJ) magnetic resonance imaging (MRI) to identify sacroiliitis in CD patients and its association with clinical and serological markers. Methods Consecutive adult subjects with CD prospectively enrolled from an inflammatory bowel disease clinic underwent SIJ MRI. Data collected included CD duration, history of joint/back pain, human leukocyte antigen‐B27 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(48 reference statements)
0
2
1
Order By: Relevance
“…The further studies showed a feasibility of MRE to detect BME, sclerosis, fatty deposits, and also to some extent erosions with ankylosis 6,13,14,34 . However, studies in patients with inflammatory bowel disease, especially with CD, based either on MRE or on MRI, found no significant association between SIJ changes and clinical parameters such as disease duration, behavior, bowel involvement, and BMI 6,13,14,34–37 . We also did not find any significant difference in the abovementioned clinical parameters between CD patients with and without SIJ changes.…”
Section: Discussioncontrasting
confidence: 49%
“…The further studies showed a feasibility of MRE to detect BME, sclerosis, fatty deposits, and also to some extent erosions with ankylosis 6,13,14,34 . However, studies in patients with inflammatory bowel disease, especially with CD, based either on MRE or on MRI, found no significant association between SIJ changes and clinical parameters such as disease duration, behavior, bowel involvement, and BMI 6,13,14,34–37 . We also did not find any significant difference in the abovementioned clinical parameters between CD patients with and without SIJ changes.…”
Section: Discussioncontrasting
confidence: 49%
“…Kelly et al [17] reported association of sacroiliitis with male sex, history of peripheral arthritis and Crohn's disease inflammatory phenotype [17]. Standardized MRI of sacroiliac joint (SIJ) showed sacroiliitis in 12-39% of patients with IBD [23][24][25][26] and this wide range was again due to differences in MRI interpretations in these studies (e.g. ASAS definition of MRI positivity vs. inclusion/exclusion of structural lesions).…”
Section: Prevalence Of Inflammatory Bowel Disease Associated Sacroili...mentioning
confidence: 99%
“…These findings might suggest that subclinical gut inflammation in axSpA patients is similar to Crohn's disease. Conversely, only 4% of patients with IBD develop AS with higher incidence associated with longer duration of IBD and up to 40% Crohn's disease patients were found to have sacroiliitis on MRI-based studies [24,25].…”
Section: Pathogenesis Of Inflammatory Bowel Disease Associated Arthritismentioning
confidence: 99%